Dostoyevsky's Stalker and other essays on psychopathology and the arts - Sperber, Michael 1931- (IG library, 2010)
In Dostoyevsky's Stalker, we discover how the arts may illuminate psychiatry and psychoanalysis, as well as how these disciplines may elucidate works of literature, art, and cinema. Examining a diversity of authors, artists, historical figures, and psychopaths over the course of modern history, this groundbreaking collection of essays proposes a paradigm shift in psychiatry, based on the idea that some symptoms of mental illness may have constructive uses and may be used by the sufferer for mental and spiritual growth instead of going untreated or else being "analyzed away."